Advances in 3D Sensor Technology by Using Stepper Lithography - Boscardin, Maurizio; Ferrari, Sara; Ficorella, Francesco; Lai, Adriano; Mendicino, Roberto; Meschini, Marco; Ronchin, Sabina; Samy, Md. Arif Abdulla; Dalla Betta, Gian-Franco (Frontiers in Physics, 2021)
3D pixel sensors aimed at the upgrades of the ATLAS and CMS experiments at the High Luminosity LHC have small pixel size and pretty dense layouts. In addition, modified 3D designs with small pixel size and trenched electrodes in place of columnar electrodes are being developed to optimize the pixel timing performance in view of the LHCb upgrade. The fabrication of these advanced 3D pixels is challenging from the lithographical point of view. This motivated the use of stepper lithography at FBK in place of a standard mask aligner. The small minimum feature size and high alignment accuracy of stepper allow a good definition of the sensor geometries also in the most critical layouts, so that a higher fabrication yield can be obtained. In this paper, we will present the main design and technological issues and discuss their impact on the electrical characteristics of 3D pixel sensors of different geometries.